Content Analysis in the English Textbook “Bahasa Inggris” for the eleventh grade Students of Senior High School - 12, Yuvia (Journal Of Foreign Language Learning and Teaching, 2022)
The purpose of this study was to analyze and determine the suitability and suitability of the contents of the teaching materials in the form of "Bahasa Inggris" textbooks used during the learning and teaching process based on textbook evaluation criteria in the opinion of experts, namely Cunningsworth (1995). This study uses a descriptive qualitative method with content analysis based on Cunningsworth's theory. Data was collected from a textbook entitled "Bahasa Inggris" for grade eleventh students at SMAN 1 Timpah published by the Indonesian Ministry of Education and Culture by reading material that focuses on content analysis. The focus of this study is to analyze 2 chapters of an English textbook. The results of the study prove that the contents of a textbook entitled Bahasa Inggris can be said to be good and meet the Cunningsworth criteria and curriculum standard 13.